RGD‐Peptide‐Modified NaLuF4:Yb, Er Nanocrystals for Upconversion‐Luminescence‐Targeted Tumor‐Cell Imaging. Issue 44 (23rd October 2017) - Yang, Tianshe; Wang, Yemao; Gao, Hui; Liu, Qian; Zhang, Kenneth Yin
Abstract : Upconversion NaLuF4 nanophosphors (UCNPs), with excellent upconversion luminescence (UCL) and good biocompatibility, have been synthesized by the solvothermal method. The surfaces of the NaLuF4 UCNPs have been modified with the tripeptide arginylglycylaspartic acid (RGD) for targeting tumor cells, based on their high and specific affinity to the transmembrane receptor αv β3 integrin. The morphology, size, and UCL properties of the UCNPs have been investigated in detail. The methyl thiazolyl tetrazolium assay suggests low cytotoxicity of the UCNPs to tumor cells and normal cells, indicative of their suitability for bioapplications. The RGD‐modified NaLuF4 nanocrystals have been used for UCL‐targeted cell imaging in U87MG tumor cells. The results demonstrate that RGD modification yields NaLuF4 UCNPs suitable for UCL‐targeted cell imaging under excitation at 980 nm, owing to the high and specific affinity between RGD and αv β3 integrin. Abstract : RGD‐peptide‐modified NaLuF4 :Yb, Er nanocrystals exhibit intense upconversion luminescence and are used for targeted imaging of U87MG cells.